Índice digital d2:d4 medido en ambas manos como factor pronostico del desarrollo del lenguaje en el niño(a) de 2 a 5 años de edad - Rodríguez Chávez, Jhon Lenin (2017)
INTRODUCTION: The hormonal influence is being suggested in the child's language development, in which testosterone is related to a better development of the latter. Testosterone and estrogens are related to the digital index D2: D4, which determines a negative relation for the first (low index in men) and positive for the second (high index in women). The objective of the study chose the digital index D2: D4 as a prognostic factor of language development. MATERIALS AND METHODS: A cross-sectional and correlational study was carried out in which a child 97 (boy) 2-5 years of age measured the index finger length (D2) and the ring finger (D4) to find The ratio D2: D4. The instrument of the Language Development Survey was reached for the parents in question. Statistical analysis of simple regression is used to analyze the data. RESULTS: Differences were found in the digital index (lower in children and higher in girls), which was significant for left hands (p = 0.044). The moderate negative correlation was found for language development as measured by the Language Development Tool (SDL); In left hands, in 5-year-old girls (r = -0.677), statistically significant (p = 0.004). CONCLUSION: The left hand D2: D4 low index would be a predictor of adequate language development as measured by the Language Development Tool (SDL) in 5-year-old girls.